Peran Pemerintah Daerah Dalam Penegakan Peraturan Daerah Agar Terwujudnya Pemerintah Daerah yang Baik (Good Government) - Dion A.F Siallagan; Glosalia Siregar (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The concept of Regional Government comes from the translation of Local Goverman which basically contains three meanings, namely: First means local government, Second: means local government, Third: means local area. The definition of local in the first sense refers to organizations/institutions/bodies whose function is to administer regional government. Local understanding in the second sense, government activities carried out by the Regional Government. The definition of local in the third sense refers to an autonomous region or region. The granting of authority (devolution of authority) to regional governments is an absolute necessity and cannot be avoided. The positive aspect of giving authority to the Regional Government is that the tasks of the government will be carried out better, because the people in the area already understand the context of social, economic and political life around their environment. The Regional Government fully understands the needs of its people and how to mobilize its resources and sources of funds. In order to realize good local government (Good Government) and in accordance with the regional autonomy mission contained in Law Number 23 of 2014 concerning regional government which accommodates community involvement in the framework of increasing development.